Serotype switching in Pseudomonas aeruginosa ST111 enhances adhesion and virulence. - Mikkel Anbo; Mahbuba Akter Lubna; Dina A Moustafa; Telmo O Paiva; Laura Serioli; Kinga Zor; Claus Sternberg; Katy Jeannot; Oana Ciofu; Yves F Dufrêne; Joanna B Goldberg; Lars Jelsbak (PLoS Pathogens)
Evolution of the highly successful and multidrug resistant clone ST111 in Pseudomonas aeruginosa involves serotype switching from O-antigen O4 to O12. How expression of a different O-antigen serotype alters pathogen physiology to enable global dissemination of this high-risk clone-type is not understood. Here, we engineered isogenic laboratory and clinical P. aeruginosa strains that express the different O-antigen gene clusters to assess the correlation of structural differences of O4 and O12 O-antigens to pathogen-relevant phenotypic traits. We show that serotype O12 is associated with enhanced adhesion, type IV pili dependent twitching motility, and tolerance to host defense molecules and serum. Moreover, we find that serotype O4 is less virulent compared to O12 in an acute murine pneumonia infection in terms of both colonization and survival rate. Finally, we find that these O-antigen effects may be explained by specific biophysical properties of the serotype repeat unit found in O4 and O12, and by differences in membrane stability between O4 and O12 expressing cells. The results demonstrate that differences in O-antigen sugar composition can affect P. aeruginosa pathogenicity traits, and provide a better understanding of the potential selective advantages that underlie serotype switching and emergence of serotype O12 ST111.